Cobalt-based crystalline catalyst with three-dimensional porous structure as well as preparation method and application of cobalt-based crystalline catalyst

By preparing a cobalt-based crystalline catalyst with a three-dimensional porous structure, the problems of strict reaction conditions and low yield of the traditional olefin oxidation alkylation method are solved, and the oxidation and alkylation reaction of styrene is efficiently achieved, with high yield and the catalyst recyclable.

CN119771500AActive Publication Date: 2025-04-08SHANGHAI INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411729286.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-08
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The traditional olefin oxidation alkylation method has problems such as strict reaction conditions, low yield and large by-products, which limits its wide application.

Method used

A cobalt-based crystalline catalyst with a three-dimensional porous structure is provided, formed by a mixed ligand composed of 2,4,6-tri(4-pyridyl)-1,3,5-triazine and D-camphoric acid and is assembled with Co(II), and prepared by hydrothermal method.

Benefits of technology

The catalyst has a large specific surface area, multiple active sites, and high catalytic activity. It especially shows high catalytic efficiency in the oxidative alkylation reaction of styrene. The maximum separation yield can reach 88%, and the catalyst can still maintain a catalytic efficiency of 85% after 10 recycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771500A_ABST
    Figure CN119771500A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt-based crystalline catalyst with a three-dimensional porous structure as well as preparation and catalytic application of the cobalt-based crystalline catalyst, and the cobalt-based crystalline catalyst is a porous cobalt-based crystalline catalyst formed by assembling a mixed ligand of D-camphoric acid (D-cma) and 2, 4, 6-tri (4-pyridyl)-1, 3, 5-triazine (4-TPT) with cobalt nitrate hexahydrate Co (NO3) 3.6 H2O under a solvothermal condition. The invention provides a preparation method of the catalyst, which comprises the following steps: mixing a mixed ligand and cobalt nitrate, transferring into a hydrothermal kettle, carrying out solvothermal reaction, and carrying out suction filtration, washing, drying and separation to obtain the Co (II)-based crystalline material, the crystalline material provided by the invention has a relatively large specific surface area and a relatively large conjugated system, and has relatively high catalytic activity on an oxidative alkylation reaction of styrene, and the highest separation yield can reach 88%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cobalt-based crystalline catalysts, and specifically relates to a cobalt-based crystalline catalyst with a three-dimensional porous structure and a preparation method and application thereof. Background Art

[0002] The difunctionalization reaction of olefins is an important research direction in organic chemistry. It increases the diversity and function of organic compounds by introducing two functional groups, and provides the required raw materials for new drug development, material manufacturing and polymer synthesis. Among them, oxidative alkylation is a common way to difunctionalize olefins. It can convert olefins into difunctional compounds containing carbonyl and alkyl in a one-step reaction, simplifying the synthesis process and improving the structural accuracy of the product. As an important functional group, carbonyl has a wide range of applications in the fields of medicine and materials, and has become a key element in the design of new drugs and the preparation of high-performance materials. However, traditional oxidative alkylation methods have problems such as strict reaction conditions, low yields, and a large number of by-products, which limit their wide application. Therefore, the development of new methods for oxidative alkylation of olefins that are efficient, environmentally friendly, and mild is of great significance for promoting the development of organic chemistry and meeting the needs of new drugs and new materials.

[0003] Patent CN 116969820A discloses a method for achieving difunctionalization of olefins by using 1,4-eneyne compounds, trifluoromethyl sources, bases and solvents. The method has mild conditions, but the process steps are complicated and the reaction time is long, which limits its application in catalytic reactions. Patent CN 117903071 A discloses a method for obtaining α-aminoketone derivatives by irradiating α-methylstyrene derivatives, azole derivatives, photocatalysts and inorganic bases under visible light. The method has mild conditions and a fast reaction time, but the yield is generally between 50-60%, which limits its application in catalytic reactions.

[0004] How to solve the traditional problems of small specific surface area, complicated preparation, low catalytic efficiency and few active sites has become an urgent problem to be solved. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a cobalt-based crystalline catalyst.

[0008] In order to solve the above technical problems, the present invention provides the following technical solution: a cobalt-based crystalline catalyst is provided, wherein the Co(II)-based crystalline catalyst is assembled from a mixed ligand and Co(II), wherein the mixed ligand is composed of 2,4,6-tri(4-pyridyl)-1,3,5-triazine and D-camphoric acid, and the Co(II) is the central ion.

[0009] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a cobalt-based crystalline catalyst.

[0010] As a preferred embodiment of the preparation method of the present invention, the method comprises:

[0011] 2,4,6-tris(4-pyridyl)-1,3,5-triazine is mixed with D-camphoric acid to form a mixed ligand;

[0012] The hydrated cobalt nitrate and the mixed ligand are mixed in a solvent under ultrasound or stirring to prepare a precursor solution;

[0013] The precursor solution is transferred into a hydrothermal reactor, and a solvent thermal reaction is carried out at 80-120° C. The Co(II)-based crystalline catalyst is obtained by suction filtration, washing and drying.

[0014] As a preferred embodiment of the preparation method of the present invention, the molar ratio of 2,4,6-tris(4-pyridyl)-1,3,5-triazine to D-camphoric acid is 1:1 to 1:2.

[0015] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the hydrated cobalt nitrate (Co(NO3)2·6H2O) to 2,4,6-tris(4-pyridyl)-1,3,5-triazine is 1:1 to 3:1.

[0016] As a preferred embodiment of the preparation method of the present invention, the solvent is a mixed solvent of N,N-dimethylformamide and ethanol.

[0017] As a preferred embodiment of the preparation method of the present invention, the volume ratio of N,N-dimethylformamide to ethanol is 1:1 to 3:1.

[0018] As a preferred embodiment of the preparation method of the present invention, the solvent thermal reaction time is 24 to 96 hours.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a cobalt-based crystalline catalyst for use in the catalytic preparation of acetophenone-based compounds.

[0020] Beneficial effects of the present invention:

[0021] 1. The Co(II)-based crystalline material obtained by the present invention has a large specific surface area, empty active sites, and high catalytic activity, especially has a high catalytic efficiency for the oxidative alkylation reaction of styrene, and the catalyst can be recycled without losing its skeleton integrity and catalytic activity.

[0022] 2. The present invention catalyzes the oxidative alkylation reaction of styrene and tetrahydrofuran, and the maximum separation yield can reach 88%. This type of material has high structural stability and good recycling effect. After recycling 10 times, the catalytic efficiency is still as high as 85%.

[0023] 3. The synthesis process of the present invention is simple, can realize the controllable assembly of catalyst materials, and has good selectivity and yield.

[0024] 4. The Co(II)-based porous crystalline catalyst material synthesized in the present invention can solve the shortcomings of the traditional method such as small specific surface area, complicated preparation, low catalytic efficiency, and few active sites. At the same time, when the catalyst is used to catalyze the oxidative alkylation reaction of styrene, it has breakthroughs such as high yield and good stability, which will greatly promote the application prospects of the synthesis of acetophenone products. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 This is a two-dimensional structural diagram of the Co(II) porous crystalline catalyst in Example 1 of the present invention.

[0027] Figure 2 This is a three-dimensional structure diagram of a single crystal of the Co(II) porous crystalline catalyst in Example 1 of the present invention.

[0028] Figure 3 This is a N2 absorption-desorption curve diagram of the crystalline catalyst in Example 1 of the present invention.

[0029] Figure 4 For the separated product in Example 6 of the present invention 1 HNMR spectrum. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.

[0034] Example 1 Synthesis of Co(II) porous crystalline catalyst

[0035] (1) weighing 2,4,6-tris(4-pyridyl)-1,3,5-triazine and D-camphoric acid in a molar ratio of 1:1 and mixing them to prepare a mixed ligand;

[0036] (2) weighing hydrated cobalt nitrate metal salt in a ratio of 1:1 between hydrated cobalt nitrate and 2,4,6-tris(4-pyridyl)-1,3,5-triazine in (1);

[0037] (3) mixing hydrated cobalt nitrate and the mixed ligand in a DMF / EtOH (volume ratio of 4:2) mixed solvent under ultrasound or stirring to prepare a precursor solution;

[0038] (4) The precursor solution is transferred into a hydrothermal reactor, and a solvothermal reaction is carried out at 80° C. for 48 hours. The Co(II)-based crystalline catalyst is obtained by suction filtration, washing, and drying.

[0039] The obtained Co(II)-based crystalline catalyst is composed of a mixed ligand of 2,4,6-tri(4-pyridyl)-1,3,5-triazine and D-camphoric acid, with Co(II) as the central ion. The mixed ligand and Co(II) are assembled to form a porous crystalline catalyst with a three-dimensional structure.

[0040] The diffraction intensity data were collected on a BrukerAPEX II diffractometer to obtain the coordination structure of the catalyst. The Co(II) central ion in the material was connected to four carboxyl oxygen atoms from D-camphoric acid and a pyridine nitrogen atom from 2,4,6-tri(4-pyridyl)-1,3,5-triazine to form a five-coordinated tetrahedral configuration, as shown in Figure 2. Figure 1As shown, two symmetry-related Co(II) centers are bridged by four carboxyl groups to form a stable binuclear paddle-wheel unit of Co2(OCO)4, which is connected by D-camphoric acid to form a two-dimensional layered structure, which is further connected by 4-TPT to form a porous material with a three-dimensional structure, as shown in Figure 2 As shown, two of the three pyridines in 2,4,6-tri(4-pyridyl)-1,3,5-triazine participate in the construction of the structure, and the remaining pyridine nitrogen atom containing a lone pair of electrons does not participate in the coordination and extends to the center of the pore, so that it can contact the guest molecule well and serve as a Lewis base catalytic center; at the same time, the Co(II) center acts as a Lewis acid to further catalyze the oxidative alkylation reaction.

[0041] Figure 3 The N2 adsorption-desorption isotherm curve of the sample obtained in Example 1 is disclosed. Experimental tests show that the obtained porous material has a large specific surface area. BET =856.4m 2 / g.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the solvent thermal reaction is carried out at a temperature of 100° C. for 48 hours, and the other steps are the same.

[0044] Example 3

[0045] The difference between this embodiment and embodiment 1 is that: in step (2) of this embodiment, the hydrated cobalt nitrate metal salt is weighed in a molar ratio of 2:1 between the hydrated cobalt nitrate and the 2,4,6-tri(4-pyridyl)-1,3,5-triazine in (1), and in step (4) of this embodiment, the solvent thermal reaction is carried out at a temperature of 100° C. for 96 hours, and the other steps are the same.

[0046] Example 4

[0047] The difference between this embodiment and embodiment 1 is that: in step (2) of this embodiment, the hydrated cobalt nitrate metal salt is weighed in a molar ratio of 3:1 between the hydrated cobalt nitrate and the 2,4,6-tri(4-pyridyl)-1,3,5-triazine in (1), and in step (4) of this embodiment, the solvent thermal reaction is carried out at a temperature of 120° C. for 24 hours, and the other steps are the same.

[0048] Example 5

[0049] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, 2,4,6-tris(4-pyridyl)-1,3,5-triazine and D-camphoric acid are weighed in a molar ratio of 1:2, and the other steps are the same.

[0050] Example 6 Catalytic oxidative alkylation reaction of styrene and tetrahydrofuran to produce acetophenone

[0051] In the oxidative alkylation reaction of styrene and tetrahydrofuran, styrene (2 mmol) and tetrahydrofuran (20 mL) were used as reaction substrates, N-hydroxyphthalimide (NHPI, 20 mol%) was added as an initiator, 10 wt% of Co(II)-based crystalline catalyst was added to a round-bottom flask, and an oxygen balloon was added to provide an oxygen atmosphere.

[0052] The reaction mixture was heated and stirred at 65° C. on an oil bath for 12 hours, and then naturally cooled to room temperature after the reaction was completed.

[0053] The reaction mixture was poured into a sand core funnel pre-filled with diatomaceous earth for filtration, and ethyl acetate was selected as the washing solvent to fully wash the filter cake.

[0054] Subsequently, the collected filtrate was distilled under reduced pressure to remove the solvent and obtain a crude product. In order to obtain a high-purity target product, we further separated the crude product by column chromatography, using an eluent of petroleum ether:ethyl acetate in a volume ratio of 20:1, and collected the product. The solvent was removed under reduced pressure on a rotary evaporator, the product was dried, and weighed to calculate the yield. The product was also subjected to further NMR testing, such as Figure 4 shown.

[0055] After the above reaction is completed, the catalyst can be separated and washed by simple filtration, and then the next round of catalyst recycling experiment is carried out. The specific reaction steps are the same as above. After recycling for more than 10 times, the catalytic conversion efficiency still reaches more than 85%.

[0056] Example 7

[0057] The catalytic efficiency of the catalyst for the oxidative alkylation reaction of styrene containing different substituents is shown in the following reaction equation:

[0058]

[0059] The experimental results are shown in Table 1 (wherein R represents a substituent), and the results show that the catalyst has a high catalytic efficiency for the oxidative alkylation reaction of styrene with different substituents.

[0060] Table 1

[0061]

[0062]

[0063] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A cobalt-based crystalline catalyst, characterized in that: The Co(II)-based crystalline catalyst is assembled from a mixed ligand and Co(II), wherein the mixed ligand is composed of 2,4,6-tris(4-pyridyl)-1,3,5-triazine and D-camphoric acid, and the Co(II) is a central ion.

2. The method for preparing the cobalt-based crystalline catalyst according to claim 1, characterized in that: include, 2,4,6-tris(4-pyridyl)-1,3,5-triazine is mixed with D-camphoric acid to form a mixed ligand; The hydrated cobalt nitrate and the mixed ligand are mixed in a solvent under ultrasound or stirring to prepare a precursor solution; The precursor solution is transferred into a hydrothermal reactor, and a solvent thermal reaction is carried out at 80-120° C. The Co(II)-based crystalline catalyst is obtained by suction filtration, washing and drying.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the 2,4,6-tris(4-pyridyl)-1,3,5-triazine to D-camphoric acid is 1:1 to 1:

2.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the hydrated cobalt nitrate to 2,4,6-tris(4-pyridyl)-1,3,5-triazine is 1:1 to 3:

1.

5. The preparation method according to claim 2, characterized in that: The solvent is a mixed solvent of N,N-dimethylformamide and ethanol.

6. The preparation method according to claim 2 or 5, characterized in that: The volume ratio of the N,N-dimethylformamide to ethanol is 1:1 to 3:

1.

7. The preparation method according to claim 2, characterized in that: The solvent thermal reaction time is 24 to 96 hours.

8. Use of the cobalt-based crystalline catalyst according to claim 1 in catalytic preparation of acetophenone-based compounds.

Citation Information

Patent Citations

  • Co-M-B amorphous alloy nanotube catalyst, and preparation and application thereof

    CN103272611A

  • A pyridyl bistriazine metal complex as well as preparation and application thereof

    CN109867701A

  • Chiral ligand exchange type COF-coated MOF / L composite material and preparation method thereof

    CN112604659A

  • Preparation method of aryl sulfonyl fluoride and aryl sulfonium salt as substrate

    CN117024312A

  • A continuous process for production of polymeric materials

    SG134810A1